PENGEMBANGAN MODUL PEMBELAJARAN FISIKA MENGGUNAKAN PENDEKATAN SAINTIFIK - Alpi Zaidah; Suratman Wijaya (LPPM Institut Pendidikan Nusantara Global, 2021)
This research aims to: (1) developing physics module based on scientific to improve student’s critical thinking competency, (2) knowing the appropriateness of physics learning module based on scientific. The research type that is used is the type of development research (Research and Development), and the model of module development that is used is 4-D (four D model) consisting of Define, Design, Develop and Disseminate that is stated by Thiagarajan. The learning module based on scientific is arranged for the learning participants actively construct the concept, the law or principle through 5 stages of 5 M which are mengamati (observing), menanya (interviewing), mencoba (trying), menalar (reasoning), and mengkomunikasikan (communicating). The module is judged based on the appropriateness of material, media, and language and limited trials and wide trials to the student and the stage of spread in the MGMP forum. The data collection uses the questionnaire of necessity analysis, the form of module validation, the questionnaire of trial response (limited and spacious), the questionnaire of disseminate response, and the test of critical thinking. The results of the research are as follow: (1) physics module based on scientific to improve the student’s critical thinking competency having a characteristic which is learning the learning stage on the module is adapted with scientific learning stage in each of the stage and loads the test question of critical thinking, (2) the module is categorized feasible with the counting result (material expert, media expert, linguist, teacher, and colleague) showing the average value which is 85 >cut off 84. Also, it is supported by the student’s positive response and the disseminate result that is conducted in MGMP forum that categorizes that the module is very good. Based on the research it can be concluded that the physics module based on scientific to improve the students’ critical thinking competency that is developed is feasible to use as the source of physics learning source.